ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA MTs KELAS VII PADA MATERI SEGITIGA DAN SEGIEMPAT - Muhamad Jalaludin; Euis Eti Rohaeti; M Afrilianto (IKIP Siliwangi, 2018)
This study aims to determine the ability of mathematical connections of students of class VII MTs on triangular and rectangular materials. The type of research used is adapted to the approach that is descriptive research type. The subjects were 5 MTs students. Data collection techniques in this study using test techniques. The results of students' written test are to solve the problem of 5 items. Data analysis is done to analyze students' mathematical connection ability. The average percentage of students' mathematical ability in solving test questions given by the researchers as much as 5 items that are with percentage 36%. So it can be concluded that the mathematical connections of students of MTs on triangle and rectangle materials are still relatively low. This is shown in the test of mathematical connection ability of students have not been able to connect the problem well. Students do not understand how to apply a concept with other concepts, apply the concept to everyday life, apply it to triangle and quadrilateral problem so that students have difficulties in solving problems, difficulties in understanding about making students confused in interpreting the sentence in question.